Effects of Non-Metallic Inclusions and Mean Stress on Axial and Torsion Very High Cycle Fatigue of SWOSC-V Spring Steel - Ulrike Karr; Bernd M. Schönbauer; Yusuke Sandaiji; Herwig Mayer (Metals, 2022)
Inclusion-initiated fracture in high-strength spring steel is studied for axial and torsion very high cycle fatigue (VHCF) loading at load ratios of R = −1, 0.1 and 0.35. Ultrasonic S-N tests are performed with SWOSC-V steel featuring intentionally increased numbers and sizes of non-metallic inclusions. The fatigue limit for axial and torsion loading is considered the threshold for mode I cracks starting at internal inclusions. The influence of inclusion size and Vickers hardness on cyclic strength is well predicted with Murakami and Endo’s <semantics><msqrt>area</msqrt></semantics> parameter model. In the presence of similarly sized inclusions, stress biaxiality is considered by a ratio of torsion to axial fatigue strength of 0.86. Load ratio sensitivity is accounted for by the factor ((1 − R)/2)α, with α being 0.41 for axial and 0.55 for torsion loading. VHCF properties under torsion loading cannot appropriately be deduced from axial data. In contrast to axial loading, the defect sensitivity for torsion loading increases significantly with superimposed static mean load, and no inclusion-initiated fracture is found at R = −1. Size effects and the stress gradient effective under torsion loading are considered to explain smaller crack initiating inclusions found in torsion ultrasonic fatigue tests.